Biological Leaching Of Manganese Ores - E. G. Noble (Society for Mining, Metallurgy & Exploration, 1991)
Microbial leaching is being investigated as a method for recovering the metal values from a domestic low-grade manganese wad ore. Early work showed that heterotrophic microorganisms present in the ore solubilized manganese when cultured in a glucose-mineral salts medium. More recent shake-flask tests using molasses as the sole nutrient source extracted 97 pct of the manganese from minus 300- µm ore in 4 weeks. Column bioleaching with the molasses medium solubilized 99 pct of the manganese from minus 6.3-mm ore in 50 weeks. The results of flask, column, and lab-scale heap bioleaching studies are presented.